Distribution of Critical Drought Areas with The Incidence of Diarrhea in East Java 2017 - Firdha Rizkhy Asedha (Universitas Airlangga, 2019)
Background: One of the factors of drought is meteorological factors, namely the influence of climate. There are two effects caused by erratic climate change namely direct effects and indirect effects. The indirect effects of which are related to infectious diseases, such as diarrhea diseases which are caused by the transmission of contaminated food and water, while water itself is closely related to drought. Purpose: This study aims to describe the distribution of critical drought areas with the incidence of diarrhea in East Java 2017. Methods: This research is a descriptive observational study with cross sectional research design. The population and samples were all patients with diarrhea and critical drought areas in East Java Province in 2017. The study sites were in East Java Province with the research period in August-October 2018. The variables studied were drought with the incidence of diarrhea. Results: The percentage of the highest critical drought areas in East Java 2017 was Sampang Regency (23%) followed by Trenggalek Regency (22%) and there were 15 Regencies/ Cities that did not experience critical drought in East Java 2017. While the incidence of diseases diarrhea in East Java 2017 was the highest in Sidoarjo Regency (65,543 cases) followed by Mojokerto Regency (64,468 cases), and the lowest incidence of diarrhea was in Probolinggo City (254 cases). Conclusion: Distribution of critical drought areas does not affect the incidence of diarrhea in East Java 2017.